2017
DOI: 10.1371/journal.pone.0185435
|View full text |Cite
|
Sign up to set email alerts
|

Complicated malaria in children and adults from three settings of the Colombian Pacific Coast: A prospective study

Abstract: BackgroundComplicated malaria remains an important public health problem, particularly in endemic settings where access to health services is limited and consequently malaria fatal outcomes occur. Few publications describing the clinical course and outcomes of complicated malaria in Latin America are found in the literature. This prospective study approached the clinical and laboratory characteristics of hospitalized patients with complicated malaria in different endemic areas of the Colombian Pacific Coast wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
2
22
2
Order By: Relevance
“…The second set of samples (set 2) was obtained from a passive case detection study conducted from 2011 to 2013 at malaria points of care ( 15 ) and from 2014 to 2016 in hospitals ( 51 ) of Quibdó, Tumaco, and Tierralta. Samples from children (set 2a) and men (set 2b) with acute P. vivax or P. falciparum malaria as well as a set of plasma samples from pregnant women with P. vivax or P. falciparum malaria ( 51 , 52 ) (set 2c) were included.…”
Section: Methodsmentioning
confidence: 99%
“…The second set of samples (set 2) was obtained from a passive case detection study conducted from 2011 to 2013 at malaria points of care ( 15 ) and from 2014 to 2016 in hospitals ( 51 ) of Quibdó, Tumaco, and Tierralta. Samples from children (set 2a) and men (set 2b) with acute P. vivax or P. falciparum malaria as well as a set of plasma samples from pregnant women with P. vivax or P. falciparum malaria ( 51 , 52 ) (set 2c) were included.…”
Section: Methodsmentioning
confidence: 99%
“…However, this method was tested without success [44]. More recently, a study conducted in South America showed that thrombocytopenia was one of the most altered hematological parameters in severe infections, regardless of species, with 90% of patients having platelet counts lower than 150,000/ μL and 43% of the population surveyed were < 50,000/ μL [46].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperparasitaemia leads to destruction of host erythrocytes, consumption of host glucose, stimulation of lactate formation through hypoxia and alteration of erythrocyte membrane transport systems [ 23 ]. Thus infants exposed in utero to parasite antigens may be at higher risk of serious complications associated with malaria infection despite the fact that other factors may be at play in influencing levels of parasitaemia.…”
Section: Main Textmentioning
confidence: 99%